2015
DOI: 10.3906/zoo-1408-8
|View full text |Cite
|
Sign up to set email alerts
|

Description of the new species Chthonius (Ephippiochthonius) negarinae sp. nov. (Pseudoscorpiones: Chthoniidae) from Iran

Abstract: A new species, Chthonius (Ephippiochthonius) negarinae sp. nov., is described from Iran. In addition, illustrations and measurements are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The family Chthoniidae Daday 1889 is poorly represented in the Caucasus, the Middle East and central Asia, and the genus Ephippiochthonius (Beier 1930) currently contains only seven named species from this area (Table 1) (Harvey 2013;Nassirkhani & Vafai 2015). In this contribution, a new pseudoscorpion species belonging to the genus Ephippiochthonius was discovered in soil of common yew trees, Taxus baccata, and evergreen trees, Buxus spp., locating in a yew-boxtree grove of the Caucasian State Nature Biosphere Reserve.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The family Chthoniidae Daday 1889 is poorly represented in the Caucasus, the Middle East and central Asia, and the genus Ephippiochthonius (Beier 1930) currently contains only seven named species from this area (Table 1) (Harvey 2013;Nassirkhani & Vafai 2015). In this contribution, a new pseudoscorpion species belonging to the genus Ephippiochthonius was discovered in soil of common yew trees, Taxus baccata, and evergreen trees, Buxus spp., locating in a yew-boxtree grove of the Caucasian State Nature Biosphere Reserve.…”
Section: Introductionmentioning
confidence: 93%
“…anatolicus (Beier 1969) Iran -Turkey E. iranicus (Beier 1971) Iran E. romanicus (Beier 1935) Greece -Iran -Romania -Turkey E. negarinae (Nassirkhani & Vafai 2015) E. sacer (Beier 1963) Iran Israel ly (Fig. 3); serrula exterior with 12-15 blades (♀♂); serrula interior with 9-10 blades (♀♂); fixed finger with 8-10 distinct teeth, basal teeth smaller than apical teeth (♀♂); movable finger with 6-8 teeth (♀♂), sub-apical tooth largest and situated separately from others, basal teeth very small, teeth become larger gradually from base to apical margin of finger (Fig.…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be clearly separated from the epigean E. caucasicus (described from Sochi, 1. [Preyssler, 1790], it has been repeatedly shown that this supposedly most widely distributed and frequently recorded species among the pseudoscorpions (see e.g, Harvey [1991]; WPC [2022]) is actually a complex of species, the E. tetrachelatus-group (see Gardini [2013]), with many new species described recently [Gardini, 2013;Zaragoza, 2017;Nassirkhani, Shoushtari, 2015;Nassirkhani et al, 2019;Kolesnikov et al, 2019;Turbanov, Kolesnikov, 2021; this study]. In turn, Gardini [2013] redescribed E. fuscimanus based on the type (Italy, Trentino, Lavarone) [Simon, 1900] and other material from Italy.…”
Section: Classmentioning
confidence: 99%
“…The third pseudoscorpion species, Paramenthus shulovi, belongs to one of the smallest pseudoscorpion families (by means of species richness), which is found in xeric habitats, Menthidae, comprising five genera. Paramenthus shulovi was the first member of the family to be found outside America; but, in 2007, Mahnert described from Socotra Island, Yemen, a second Paramenthus species, which was later also found in south Iran [39,40]. Thus, the genus Paramenthus is assumed to be Paleoeremic and of Afrotropical origin.…”
Section: Endemismmentioning
confidence: 99%